SWOT ANALYSIS IN THE DEVELOPMENT OF GOVERNMENT GRANTS FROM KEDIRI REGENCY FOR GOAT FARMING GROUPS - Syaifulloh Ibnu Alam Nurzaman; Siti Azizah; Achadiah Rachmawati; Bara Ismiaji (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to evaluate the strategic development of the government grant program for goat farming groups in Kediri Regency through a SWOT analysis approach. The program, launched in 2022, serves as an economic empowerment initiative to support small-scale farmers by increasing livestock populations and improving rural welfare. Data were collected using a descriptive quantitative method through in-depth interviews with program managers and grant recipients, supported by direct field observations. The Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices were used to determine the program’s strategic position, while the Cartesian SWOT diagram identified the appropriate development quadrant. The results show that the program is situated in Quadrant II, indicating strong internal conditions but significant external threats. With IFE and EFE scores of 2.9252 and 3,1333 respectively, the analysis suggests that the program should implement Strength–Threat (S-T) strategies, including consistent quarterly reporting, increased technical staff, and public reinforcement of the program’s catalytic function. These findings are expected to guide the formulation of more effective strategies for sustainable livestock empowerment in Kediri Regency.